Sequential fractionation and plant availability of heavy metals as affected by sewage sludge applications to soil - Canet, Rodolfo; Pomares, Fernando; Tarazona, Francisco; Estela, María (Taylor & Francis, 2021)
The effect of sewage sludge applications on extractability and uptake by chard and lettuce of soil cadmium (Cd), chromium (Cr), copper (Cu), nickel (Ni), leaf (Pb), and zinc (Zn) was investigated. Ten different treatments (0, 150, 300, and 500 kg N ha‐1) as mineral fertilizer, and 400, 800, and 1,200 kg N ha‐1 of aerobically and anaerobically‐digested sewage sludges were applied annually to a sandy‐loam soil since 1984. Seven years after the start of the treatments, higher levels of heavy metals were detected in the soil, depending on the type of metal, depth of sampling, type of sludge used, and, especially, rate of application. Following a sequential extraction procedure incorporating 0.1M CaCl2, 0.5M NaOH, and 0.05M Na2EDTA, most of the heavy metals in soil were detected in the Na2EDTA solution and the residual fractions. Large amounts of Cd appeared to be extracted by CaCl2, whereas substantial amounts of Cu and Ni were isolated by NaOH. The effect of treatments on the percentages of the metals found in each fraction depended on the type of metal, sampling depth, sludge used, and application rate. No significant increases were found in the heavy metal contents of chard and lettuce leaves, but some of the treatments resulted in a significant decrease of Cd and Cr levels in lettuce leaves.